La Formación De Profesionales De La Agricultura Y La Sostenibilidad - Hilter Figueroa Saavedra; Luis Fiallos; Arisdorgan Diéguez Almaguer (European Scientific Journal, ESJ, 2018)
This paper focuses on contributing to the formation of future professionals of agriculture from a different perspective. As a result, the theoretical, empirical, and statistical analysis methods were used according to the research. These methods deal with the ecological worldwide problems such as; climatic change, greenhouse effect, global warming, water crisis, and, at the same time, how agriculture is affected by those problems. The use of various techniques and predators methods of production has contributed in worsening the situation. Alternative methods were presented to reduce the negative effect of agriculture on the ecosystems. This, therefore, would help to finally offer a didactic, dynamic, and participative model for the training of professionals through university - society relationship.